Pengaruh Promosi Penjualan Dan Persediaan Terhadap Keputusan Pembelian Dengan Harga Sebagai Variabel Mediasi Studi Pada Pelanggan Toko “Salah Parkir” Classic Part & Custom Kota Metro - M. Azzam Nurkholis; Suwarto; Ardiansyah Japlani (Jurnal Manajemen DIVERSIFIKASI, 2025)
In order to win the competition, each entrepreneur carries out their own marketing strategy,among the marketing strategies that are generally implemented by each company includeincreasing sales promotions and providing complete stock and types of goods so that buyerswill not move to another shop that has complete stock of goods. Apart from that, settingcompetitive prices is also the key to winning the competition, because price is one of the mainconsiderations for consumers in determining where they will shop. This research aims todetermine the effect of sales promotions and inventory on purchasing decisions with price asa mediating variable for customers of the Classic Part & Custom Part & Custom Shop inMetro City. The research design is quantitative research or verification research. The objectof this research is sales promotion, inventory and purchasing decisions with price as amediating variable. The research population and sample were customers of the "SalahParkir" Classic Part & Custom Shop in Metro City with a total sample of 96 people. Datacollection techniques use questionnaires. The Analitical Tool used is data quality analysis and path analysis using the SPSS program. The research results show that sales promotions,inventory and price have a significant direct effect on customer purchasing decisions. Salespromotions and inventory have a direct and significant effect on prices. Price significantlymediates the influence of sales promotions and inventory on customer purchasing decisionsat the "Salah Parkir" Clasics Part & Custom Shop in Metro City